2022
DOI: 10.1186/s40814-022-01191-0
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted early mobilization of intensive care patients: a feasibility study protocol

Abstract: Background Early mobilization positively influences the outcome of critically ill patients, yet in clinical practice, the implementation is sometimes challenging. In this study, an adaptive robotic assistance system will be used for early mobilization in intensive care units. The study aims to evaluate the experience of the mobilizing professionals and the general feasibility of implementing robotic assistance for mobilization in intensive care as well as the effects on patient outcomes as a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Studies have shown that early mobilization is crucial in improving functional outcomes and quality of care in critically ill patients, including those in the ICU. 20 Additionally, the safety and efficacy of early mobilization have been well-documented, emphasizing its role in enhancing patient recovery and reducing the incidence of complications. 20 However, the definition of early mobilization can vary across studies, highlighting the need for standardized protocols to ensure consistency in practice and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that early mobilization is crucial in improving functional outcomes and quality of care in critically ill patients, including those in the ICU. 20 Additionally, the safety and efficacy of early mobilization have been well-documented, emphasizing its role in enhancing patient recovery and reducing the incidence of complications. 20 However, the definition of early mobilization can vary across studies, highlighting the need for standardized protocols to ensure consistency in practice and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, the safety and efficacy of early mobilization have been well-documented, emphasizing its role in enhancing patient recovery and reducing the incidence of complications. 20 However, the definition of early mobilization can vary across studies, highlighting the need for standardized protocols to ensure consistency in practice and outcomes. 21 In the context of specific conditions like hip surgery, early mobilization has been associated with better functional outcomes in the Chinese population, underscoring its positive impact on postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This project was part of the MobiStaR project (Mobilization of intensive care patients by a new standard in adaptive robotics, NCT05071248), which evaluated robotic-assisted mobilization in the surgical intensive care unit (ICU) and the reception by critical care providers [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…No matching was performed. A full list of inclusion and exclusion criteria was published with the study protocol [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…This project was part of the MobiStaR trial (Mobilization of intensive care patients by a new standard in adaptive robotics, NCT05071248), which evaluated the feasibility of robotic-assisted mobilization in the surgical intensive care unit (ICU) and the reception by critical care providers [21]. We compared ventilation duration, length of ICU stay, muscle parameters, and quality of life after 3 months with those of a conventionally mobilized control group.…”
Section: Trial Designmentioning
confidence: 99%